STRATEGI PENURUNAN STUNTING MELALUI SOSIALISASI DAN DEMONSTRASI MEMASAK OLAHAN IKAN LELE HASIL BUDIDAYA AQUAPONIK SKALA RUMAH TANGGA - Rini, S.K.; Pangestuti, E.; Putri, S.A.H.; Janah, A.N.; Aprilia, N.I.; Prastiwi, E.L.; Safitri, N.N.; Fazri, M.B.H.; Hafizh, F.R. (Buletin Udayana Mengabdi; Vol 23 No 6 (2024): Buletin Udayana MengabdiDO - 10.24843/BUM.2024.v23.i06.p04, 2024)
Stunting is a global problem that affects cognitive development and children's growth and development. The prevalence of stunting in Lamongan Regency is still high, 27.5% in 2022, based on the National Nutrition Status Survey (SSGI). The risk factor for stunting is insufficient protein intake. Efforts to reduce stunting are carried out through the fish-eating program and optimizing catfish cultivation using aquaponics on a household scale. Some people chose Catfish because it has a protein content of up to 18.7%. This community service activity aims to increase knowledge about stunting, explain the nutritional value of Catfish, and demonstrate making additional food from Catfish produced by aquaponic cultivation on a household scale. The program was conducted in June-August 2023 in Gebangangkrik Village, Ngimbang District, Lamongan Regency. This program was implemented using the Communication Information Education and Focus Group Discussion (FGD) methods for PKK mothers in Gebangangkrik Village, Ngimbang District, Lamongan Regency. The implementation results showed that knowledge of PKK mothers increased by 40%. Therefore, cooking activities can provide direct experience to PKK regarding the proper way to process Catfish. A total 20 of PKK mothers practice techniques for processing Catfish from household-scale aquaponic that are economical and environmentally friendly as additional food for toddlers. Increasing fish consumption to reduce stunting also receives support from the village government. Keywords: Aquaponic, Toddlers, Catfish, Stunting, Socialization